Determination of HIF1-Ars11549465 Polymorphism in Elite_x000D_ Skiers - ULUCAN, KORKUT (My University, 2019)
Studies in sports genetics have increased nowadays and the identification of genotype and allelic distributions of candidategenes in different athletes has provided important information to sports scientists. One of the candidate genes studied in sportsgenetics is the hypoxia-inducible factor 1-alpha (HIF1A) gene, which is associated with the endurance phenotype. In our study,we aimed to determine the genotypic and allelic distribution of HIF1A rs11549465 polymorphism in Turkish Elite cross-countryathletes. 34 (23 male, 11 female) athletes were included in the study, and 1 cc of blood samples taken for routine analysis afterthe approval of the ethics committee was used for DNA isolation. The commercial kit was used for DNA isolation andgenotyping was performed by Real-time PCR method. The number and percentage of CC, CT and TT genotypes of the HIF1Ars11549465 polymorphism were 24 (72.72%), 8 (24.24%) and 1 (3.03), respectively. In male skiers CC, CT and TT genotypenumbers and percentages were determined as 17 (55.51%), 4 (12.12%) and 1 (3.03%) respectively. In female, CC and TTgenotypes were determined as 7 (21.21%) and 4 (12.12%). We detected no TT genotype in female athletes. When we look at allelnumbers, C allele was determined as 56 (84.84%) and T allele was determined as 10 (15.15%). This is the first study on HIF1Ars11549465 polymorphism on Turkish elite ski cross-country athletes. The higher prevalence of CC genotype and C allele in theathlete group is similar to the previous studies on different groups of athletes. We believe that this study will be an importantreference for further studies.